Green synthesis of porous graphene and its application for sensitive detection of hydrogen peroxide and 2, 4-dichlorophenoxyacetic acid. (1st February 2019) - Liu, Fengping; Xu, Qin; Huang, Wei; Zhang, Zhenfa; Xiang, Gang; Zhang, Cuizhong; Liang, Caiyun; Lian, Huan; Peng, Jinyun
Abstract: This work presented a facile and green method to prepare porous graphene (PGR) using a combination of sodium citrate treatment, hydrothermal reduction and lyophilization. The structure of the obtained PGR was analyzed by X-ray diffraction spectroscopy (XRD), X-ray photoelectron spectroscopy (XPS), Brunauer-Emmett-Teller (BET), and the morphology was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Furthermore, this PGR was used as the support for the immobilization of catalase. Fourier-transform infrared spectroscopy (FT-IR) spectra indicated that the immobilized catalase kept its structure without any change. Electrochemical impedance spectroscopy and cyclic voltammetry indicated the fast electron transfer between the immobilized catalase and the glassy carbon electrode (GCE). This biosensor showed a linearity in the 1.0 × 10 −7 ∼ 7.7 × 10 −6  mol L −1 concentration range with a low detection limit of 83.0 nmol L −1 (3δ/S) for H2 O2 . In addition, the biosensor was also applied to measure 2, 4-dichlorophenoxyacetic acid (2, 4-D) concentration based on catalase enzymatic inhibition. Under the optimized conditions, two linear relationships of the inhibition ratios vs. the 2, 4-D concentrations ranging from 2.4 × 10 −9 ∼ 2.6 × 10 −8  mol L −1 and 2.6 × 10 −8 ∼ 3.6 × 10 −7  mol L −1 were found. The detection limit for 2, 4-D was down to 1.5 nmol L −1 at 3δ/S. The inhibition constants ( K i ) of 2, 4-D to the immobilized catalase was calculated to be 6.50 × 10 −8  mol L −1 . This biosensor was applied for the determination of H2 O2 and 2, 4-D in real samples with satisfactory results. Graphical abstract: A sensitive biosensor for the H2 O2 and 2, 4-dichlorophenoxyacetic acid (2, 4-D) determination was achieved based on catalase immobilized on PGR. Image 1 Highlights: Sodium citrate and hydrothermal reduction were combined to prepare PGR. The PGR was served as a novelty immobilization matrix for catalase. H2 O2 and 2, 4-D detections were realized based on the immobilized catalase. The PGR based sensor showed improved sensitivity and selectivity.